PERUMUSAN STRATEGI TEKNOLOGI UNTUK MENINGKATKAN KINERJA UNIT KHUSUS PENGELOLAAN INSTITUSI PENDIDIKAN PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK. KANTOR CABANG PERGURUAN TINGGI BANDUNG DENGAN MENGGUNAKAN METODE SWOT ANALYSIS DAN SFAS MATRIX - Andrea, Yose (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
Level of banking competition is increasingly high demands on banks to focus more on the desired target market. PT. Bank Negara Indonesia (Persero) Tbk, Universities Branch Office Bandung (BNI PTB) is one branch in the city of Bandung which has a core business in Corporate Banking particular educational institution. To better focus on its managed, BNI PTB forming units specialized to manage the educational institutions managed. The existence of this unit is not specifically regulated as other units in BNI organization structure, because this unit is the only unit that is in BNI. Based on the above conditions, to maximize the existence of this special unit investigators interested in conducting research on this unit at BNI PTB and analyze strategic variables in the environment both external strategic environment and internal strategic environment. A number of respondents involved in this study consisted of the employees and management of branch offices and regional office management and after the selection of respondents, 20 respondents was selected to be part of the study, starting from the interviews, questionnaires phase 1 and phase 2 questionnaire. Identification results through the interview concluded several variables that affect the operation and performance of this particular unit. External variables, namely the growth of business education market in the city of Bandung, the factors of competition between banks and the development of technology to support quality of service to the Institute of Education, while internal factors consist of variables of Human Resources (HR), Information Systems Technology and Operations in the special unit itself. After analysis of the strategic variables by using a SWOT Analysis, SFAS Matrix and IE Matrix concluded that indicators of variable performance that is very supportive of this special unit and in line with the existence of this special unit in the IE matrix in cell 2 (growth strategy) with the concentration of horizontal integration through market expansion and internal development of technology in special units in order to facilitate the work. It can be concluded that the formulation of the availability of Information Technology has been defines the constraints faced by the special operations unit that could be addressed to improve the BNI Business PTB Branch Office and can also overcome the problems of existing human resources that have a positive impact on the performance of BNI Branch PTB as well as expected can accelerate and enhance the quality of better service to educational institutions. Keywords: Special Unit for Management of Educational Institutions, PT. Bank Negara Indonesia Tbk. Universities Branch Office Bandung, Strategic Management, Corporate Strategy, SWOT Analysis, SFAS Matrix, Matrix Internal External